Removal of Phosphorus from Domestic Wastewater by Using L-shape Semi Aerated Steel Slag Filter System. Issue 1 (1st May 2022) - Hamdan, R.; Ayub, K A; Arshad, N A N M
Abstract: Excessive amount of phosphorus in wastewater prior discharged are one of the major cause of eutrophication in lakes and rivers making phosphorus removals are essentials. However, removing phosphorus from wastewaters required a high cost treatment system to be installed at treatment facilities. To provide alternative solutions, this study was conducted to investigate the effectiveness of L-shape semi aerated filter with steel slag as filter media to provide a cost effective treatment system using natural media as a solution to remove phosphorus from domestic wastewater. The L-shaped semi aerated filter was constructed and installed onsite at Sewage Treatment Plant (STP) UTHM. Then, the laboratory test was conducted twice a week to analyse five parameters including pH, turbidity, dissolved oxygen (DO), chemical oxygen demand (COD), and total phosphorus (TP). The results showed that the effluent from the L-shape steel slag filter was alkaline with a pH value range of 7.22 to 9.71 due to alkaline properties of steel slag. Turbidity value of effluent at vertical section was higher than horizontal section as it may affect the COD removal of the filter. In the vertical system, the DO value range was higher (1.5 to 6.9 mg/L) than the horizontal system (1.27 to 5.5 mg/L) since oxygen was introduced by aeration process. Furthermore, this system showed good COD removal efficiencies with values ranged from 10% to 76%. Lastly, total phosphorus removal efficiencies also showed great removals with range of 29% to 68%. From the results obtained, steel slag with high-Ca content showed excellent potential in removing phosphorus from domestic wastewater.